The evolving role of methanogenic archaea in mammalian microbiomes - Volmer, James G.; McRae, Harley; Morrison, Mark (Frontiers in Microbiology, 2023)
Methanogenic archaea (methanogens) represent a diverse group of microorganisms that inhabit various environmental and host-associated microbiomes. These organisms play an essential role in global carbon cycling given their ability to produce methane, a potent greenhouse gas, as a by-product of their energy production. Recent advances in culture-independent and dependent studies have highlighted an increased prevalence of methanogens in the host-associated microbiome of diverse animal species. Moreover, there is increasing evidence that methanogens, and/or the methane they produce, may play a substantial role in human health and disease. This review addresses the expanding host-range and the emerging view of host-specific adaptations in methanogen biology and ecology, and the implications for host health and disease.